HMGB1 Promotes Resistance to Doxorubicin in Human Hepatocellular Carcinoma Cells by Inducing Autophagy via the AMPK/mTOR Signaling Pathway - Li, Junhua; Zhou, Wei; Mao, Qiang; Gao, Dandan; Xiong, Lin; Hu, Xinyao; Zheng, Yongfa; Xu, Ximing (Frontiers in Oncology, 2021)
Chemoresistance remains as a major hindrance in the treatment of hepatocellular carcinoma (HCC). High mobility group box protein 1 (HMGB1) enhances autophagic flux and protects tumor cells from apoptosis, which results in acquired drug resistance. However, the exact mechanisms underlying HMGB1-modulated autophagy in HCC chemoresistance remain to be defined. In the present study, we found that administration of doxorubicin (DOX) significantly promoted HMGB1 expression and induced HMGB1 cytoplasmic translocation in human HCC cell lines BEL7402 and SMMC7721, which enhanced autophagy that contributes to protecting HCC cells from apoptosis and increasing drug resistance. Moreover, we observed HMGB1 translocation and elevation of autophagy in DOX-resistant BEL7402 and SMMC7721 cells. Additionally, inhibition of HMGB1 and autophagy increased the sensitivities of BEL-7402 and SMMC-7721 cells to DOX and re-sensitized their DOX-resistant cells. Subsequently, we confirmed with HMGB1 regulated autophagy by activating the 5ʹ adenosine monophosphate-activated protein kinase (AMPK)/mTOR pathway. In summary, our results indicate that HMGB1 promotes acquired DOX resistance in DOX-treated BEL7402 and SMMC7721 cells by enhancing autophagy through the AMPK/mTOR signaling pathway. These findings provide the proof-of-concept that HMGB1 inhibitors might be an important targeted treatment strategy for HCC.